Patent Foramen Ovale Implying Paradoxical Embolism as a New Insight in Cryptogenic Stroke - Indah Aprianti Putri (The Indonesian Heart Association, 2021)
Cerebrovascular thromboembolism is responsible annually for 510.000 ischaemic stroke in the united states alone. PFO mechanism as a paradoxical embolism transit from right to left-sided chambers to intracranial vessels has a tremendous impact in neurological deficits. The aggressive treatment started since 2016 when the US Food and Drug Administration (FDA) approved the Amplatzer PFO occluder for recurrent stroke prevention of cryptogenic stroke with PFO. The trials show positive results since 2017 and the collaboration and partnership between neurologist and cardiologist are more needed to build a holistic and comprehensive treatment for cryptogenic stroke patient with PFO.